Acute renal failure in the cardiac intensive care unit – A practical approach to management - Bihl, Geoffrey; Mabin, Thomas; Fine, Derek (SA Heart Journal, 2017)
The association between cardiovascular disease and acute renal failure (ARF) and acute-on-chronic renal failure is less well defined. In the cardiac intensive care unit (CICU), the presence of ARF imparts a significant mortality. The predominant aetiology of ARF in the CICU relates to hypotension, although other causes are certainly involved too, and both contrast nephropathy and cholesterol embolisation may be associated with percutaneous coronary intervention. Despite the availability of renal replacement therapies, preventative measures remain the most important element of management. Specific therapy includes management of the patient’s volume status, vasoactive medication and renal replacement therapy in the way of dialysis. In the setting of acute renal failure, both patient and renal outcome is improved with the early involvement of a nephrological service.